2002
DOI: 10.1159/000067883
|View full text |Cite
|
Sign up to set email alerts
|

Transvaginal Bone Anchors in Female Stress Urinary Incontinence: Poor Results

Abstract: Objective: This study evaluates the results of a minimally invasive technique for correcting female stress urinary incontinence by transvaginal implantation of pubic bone anchors. Patients and Methods: Female stress urinary incontinence was treated by fixing a gelatin-coated Dacron sling between two miniature titanium anchors with Prolene sutures. Results: A total of 26 patients (median age 57.2 years) underwent the sling procedure. The follow-up examination was performed after 11.4 months on average. Stress i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2004
2004
2009
2009

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In theory, this modification may reduce operating time and the morbidity of fascial harvest. Cure rates of 62% to 89% are reported in the short term, but an alarming 38% failure rate at 10.6 months also has been reported [11][12][13]. Bone anchor suspension of the sling does not appear to reduce the morbidity or complication associated with repeat SUI surgery.…”
Section: Pubovaginal Sling Failurementioning
confidence: 97%
“…In theory, this modification may reduce operating time and the morbidity of fascial harvest. Cure rates of 62% to 89% are reported in the short term, but an alarming 38% failure rate at 10.6 months also has been reported [11][12][13]. Bone anchor suspension of the sling does not appear to reduce the morbidity or complication associated with repeat SUI surgery.…”
Section: Pubovaginal Sling Failurementioning
confidence: 97%
“…More recent reports using solvent dehydrated cadaveric fascia BAS described a much lower failure rate with up to 60 months follow-up [22••]. Schostak et al [23] similarly reported poor outcomes using gelatin-coated Dacron BAS (Invista, Inc., Wichita, KS), with 65% of patients not satisfi ed after the procedure. They also reported mesh extrusion and de novo overactive bladder symptoms in 54% and 27% of patients, respectively.…”
Section: Theories Of Stress Urinary Incontinencementioning
confidence: 99%